(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Diabetes mellitus is an endocrine disease. If a person has a predisposition to diabetes or is in a risk group (for example, overweight, poor diet, sedentary lifestyle), then such conditions are observed and measures should be taken to treat it. For treatment, proper nutrition and physical exercise are mainly necessary. This article describes the causes, symptoms, diagnosis and progress in the treatment of diabetes mellitus.